Characterizing psychiatric comorbidity in children with autism spectrum disorder receiving publicly funded mental health services. (November 2018) - Brookman-Frazee, Lauren; Stadnick, Nicole; Chlebowski, Colby; Baker-Ericzén, Mary; Ganger, William
Publicly funded mental health programs play a significant role in serving children with autism spectrum disorder. Understanding patterns of psychiatric comorbidity for this population within mental health settings is important to implement appropriately tailored interventions. This study (1) describes patterns of psychiatric comorbidity in children with autism spectrum disorder who present to mental health services with challenging behaviors and (2) identifies child characteristics associated with comorbid conditions. Data are drawn from baseline assessments from 201 children with autism spectrum disorder who participated in a community effectiveness trial across 29 publicly funded mental health programs. Non-autism spectrum disorder diagnoses were assessed using an adapted Mini-International Neuropsychiatric Interview, parent version. Approximately 92% of children met criteria for at least one non-autism spectrum disorder diagnosis (78% attention deficit hyperactivity disorder, 58% oppositional defiant disorder, 56% anxiety, 30% mood). Logistic regression indicated that child gender and clinical characteristics were differentially associated with meeting criteria for attention deficit hyperactivity disorder, oppositional defiant disorder, an anxiety, or a mood disorder. Exploratory analyses supported a link between challenging behaviors and mood disorder symptoms and revealed high prevalence of these symptoms in this autism spectrum disorder population. Findings provide direction for tailoring intervention to address a broad range of clinical issues for youth with autism spectrum disorder served in mental health settings.